2010
DOI: 10.1177/104063871002200317
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Analysis of Peripheral Blood and Tumor-Infiltrating Regulatory T Cells in Dogs with Oral Malignant Melanoma

Abstract: Abstract. It is well known that tumor-infiltrating lymphocytes (TILs) and peripheral blood lymphocytes (PBLs) from patients with advanced-stage cancer have a poor immune response. Regulatory T cells (Tregs), characterized by the expression of a cluster of differentiation 4 and intracellular FoxP3 markers, can inhibit antitumor immunoresponse. In the present study, the prevalence of Tregs in peripheral blood and tumor tissue from dogs with oral malignant melanoma was evaluated by triple-color flow cytometry. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 16 publications
3
61
1
2
Order By: Relevance
“…However, it is possible that other T-cell parameters, such as vaccine-elicited T-cell phenotype, the ability to release other cytokines and the presence of cells negatively regulating the immune response, may have an impact. The immunosuppressive microenvironment at the tumor site and draining LN (48,49) may have locally inhibited the vaccine-induced immune response, allowing local recurrences and/or metastasis to other satellite LN to occur in some dogs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that other T-cell parameters, such as vaccine-elicited T-cell phenotype, the ability to release other cytokines and the presence of cells negatively regulating the immune response, may have an impact. The immunosuppressive microenvironment at the tumor site and draining LN (48,49) may have locally inhibited the vaccine-induced immune response, allowing local recurrences and/or metastasis to other satellite LN to occur in some dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, some studies have focused their investigations on dogs with tumors. [4][5][6]11,15,17 It has been described that tumor-bearing dogs have a higher number of leukocytes than normal dogs. 6 Absolute cell and relative percentage of cluster of differentiation (CD)3+ T cells, CD4+ T helper (Th) cells, CD8+ T cytotoxic (Tc) cells, and CD21+ B cells in dogs with tumors are notably decreased in comparison with healthy dogs.…”
mentioning
confidence: 99%
“…4,5 An increased population of regulatory T cells has also been reported in dogs with various cancers. 5,11,15 Despite extensive research in human beings, few reports evaluating the role of different peripheral lymphocyte subsets in dogs with non-oncologic diseases are available. In the present study, the immunophenotype found in the peripheral blood lymphocytes of dogs with several different pathologic conditions is evaluated.…”
mentioning
confidence: 99%
“…51 In these reports, dogs with all tumors studied (oral melanoma, osteosarcoma, mast cell tumor, lymphoma, and soft tissue sarcoma) showed significantly higher Treg percentages when compared to healthy animals. 3,51,81 Moreover, in oral melanomas, the percentages of Tregs were significantly increased in the tumor site when compared to peripheral blood of the same animal. The authors hypothesized that tumor cells induced either local proliferation or selective migration of Tregs to tumor-infiltrated sites.…”
Section: Tregs and Cancermentioning
confidence: 98%